Shape of LOSVDs in barred disks: implications for future IFU surveys - Li, Z; Shen, J; Bureau, M; Zhou, Y; Du, M; Debattista, V (IOP Publishing, 2018)
The shape of LOSVDs (line-of-sight velocity distributions) carries important information about the internal dynamics of galaxies. The skewness of LOSVDs represents their asymmetric deviation from a Gaussian profile. Correlations between the skewness parameter ($h_3$) and the mean velocity ($\vm$) of a Gauss-Hermite series reflect the underlying stellar orbital configurations of different morphological components. Using two self-consistent $N$-body simulations of disk galaxies with different bar strengths, we investigate $h_3-\vm$ correlations at different inclination angles. Similar to previous studies, we find anticorrelations in the disk area, and positive correlations in the bar area when viewed edge-on. However, at intermediate inclinations, the outer parts of bars exhibit anticorrelations, while the core areas dominated by the boxy/peanut-shaped (B/PS) bulges still maintain weak positive correlations. When viewed edge-on, particles in the foreground/background disk (the wing region) in the bar area constitute the main velocity peak, whereas the particles in the bar contribute to the high-velocity tail, generating the $h_3-\vm$ correlation. If we remove the wing particles, the LOSVDs of the particles in the outer part of the bar only exhibit a low-velocity tail, resulting in a negative $h_3-\vm$ correlation, whereas the core areas in the central region still show weakly positive correlations. We discuss implications for IFU observations on bars, and show that the variation of the $h_3-\vm$ correlation in the disk galaxy may be used as a kinematic indicator of the bar and the B/PS bulge.